Lake morphology and meteorological conditions impact stratification of saline lakes in the Atacama Desert - Tianshu Kong; R. Pamela Reid; Erica P. Suosaari; Daniela Maizel; Luis R. Daza; Alvaro T. Palma; Amanda M. Oehlert (PLoS ONE, 2025)
Saline lakes exist in various morphologies within salar environments, occurring as ephemeral to persistent bodies of water despite evaporative conditions. Salar environments are often characterized by strong diurnal fluctuations in temperature, UV irradiation, and wind speed, however, the extent to which these meteorological conditions impact saline lakes with different morphological characteristics has yet to be investigated. Here, we evaluate the impacts of diurnal changes in wind speed and wind direction on lake water temperature, electrical conductivity, alkalinity, and stable isotope ratios of hydrogen (δ2H), oxygen (δ18O), and sulfur (δ34SSO4) in two Na-Cl saline lakes in the Salar de Llamara (Atacama Desert, Northern Chile) with different morphologies. Results indicate that water masses in the relatively deeper (~ 0.6 m) steep-sided lake with crystalline lake bottom remained stratified despite the nearly order of magnitude increase in diurnal wind speed, while waters in the relatively shallow (< 0.2 m), gently-sloping lake colonized by microbial mats were well-mixed. Conditions in the shallow, gently-sloping lake were heterogeneous, with diurnal variations approximating 15.6% and 23.9% of known seasonal ranges in temperature and electrical conductivity, respectively. Consequently, the chemistry of shallow, gently-sloping saline lake environments is dynamic on diurnal time scales, indicating that resident microbial communities tolerate a greater range in environmental conditions than previously appreciated. Results suggest that the impacts of diurnal changes in meteorological conditions on saline lake stratification depend on lake morphology, an observation with implications for patterns of mineral deposition in salar environments.